From Likes to Loyalty: How Brand Image Translates Social Media Marketing into Lasting Customer Commitment in the Skincare Industry - Hariati Hariati; Agustinus Setyawan; Muhammad Donal Mon (Jurnal Bisnis dan Manajemen, 2026)
This study investigates the influence of brand experience and social media marketing on brand loyalty, with a specific focus on the mediating role of brand image in the context of skincare product consumption in Batam City. Data were collected from 280 users of Garnier, Pond’s, and Skintific skincare products through a questionnaire employing a Likert scale. The research utilized a quantitative methodology with a non-probability sampling technique, and the data were analyzed using Partial Least Squares Structural Equation Modeling (SEM-PLS). The findings reveal that brand experience and social media marketing both exert a significant positive influence on brand image and brand loyalty. Furthermore, brand image demonstrates a significant positive effect on brand loyalty, highlighting its critical role in fostering long-term customer commitment. An analysis of the mediating effects indicates that brand image does not significantly mediate the relationship between brand experience and brand loyalty. However, it does act as a significant mediator in the relationship between social media marketing and brand loyalty. These results suggest that a powerful brand experience can directly cultivate customer loyalty without a primary dependence on brand image. Conversely, the effectiveness of social media marketing in enhancing brand loyalty is contingent upon the successful establishment of a favorable brand image.